Hyperelastic behavior of cable gland silicon shroud: finite element analysis - Ganesh Bhoye; Ishant Jain (Academia Materials Science)
This study characterizes the hyperelastic behavior of a silicon shroud and evaluates its suitability for cable gland applications. Experimental uniaxial and biaxial stress–strain data were analyzed, and multiple hyperelastic material models were fitted to the data using a least-squares algorithm. Among the models evaluated, the Mooney–Rivlin 9-parameter (MR 9P) model best captured the material’s mechanical response under diverse loading conditions. Finite element analysis simulations were conducted to assess the shroud’s performance during radial expansion, exploring both direct and sliding expansion scenarios. The results demonstrated the silicon shroud’s excellent radial expansion capacity, achieving a maximum observed displacement of 7.5 mm while maintaining induced stresses within acceptable limits. These findings highlight the silicon shroud as a superior alternative to conventional polyvinyl chloride shrouds, offering enhanced flexibility, reduced weight, and improved environmental resistance. The hyperelastic material model developed in this study provides a robust tool for predicting the shroud’s behavior under varied loading conditions, enabling optimized designs and ensuring long-term performance.